2012
DOI: 10.1016/j.devcel.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Determinants of Neurogenesis and Myogenesis

Abstract: SUMMARY The regulatory networks of differentiation programs have been partly characterized; however, the molecular mechanisms of lineage-specific gene regulation by highly similar transcription factors remain largely unknown. Here we compare the genome-wide binding and transcription profiles of NEUROD2-mediated neurogenesis with MYOD-mediated myogenesis. We demonstrate that NEUROD2 and MYOD bind a shared CAGCTG E-box motif and E-box motifs specific for each factor: CAGGTG for MYOD and CAGATG for NEUROD2. Bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(155 citation statements)
references
References 38 publications
9
144
0
Order By: Relevance
“…The only known tissue and developmental stage that Msgn1 is expressed is in the mesenchymal cells of the PSM, making Msgn1 a remarkably stage-and tissuespecific transcription factor. Our studies demonstrate that Msgn1 regulates the EMT and PSM differentiation programs by binding to a unique E-box sequence that is distinct from the binding sites for Twist1 (Eckert et al, 2011), MyoD and NeuroD1 (Fong et al, 2012). Other non-bHLH EMT transcription factors, such as the Zn-finger homeodomain-containing factors Zeb1 and Zeb2, also function by binding to E-boxes and closely related Z-boxes (Burk et al, 2008).…”
Section: Wnt3a Regulates Emt and Psm Cell Motility Through Msgn1mentioning
confidence: 95%
“…The only known tissue and developmental stage that Msgn1 is expressed is in the mesenchymal cells of the PSM, making Msgn1 a remarkably stage-and tissuespecific transcription factor. Our studies demonstrate that Msgn1 regulates the EMT and PSM differentiation programs by binding to a unique E-box sequence that is distinct from the binding sites for Twist1 (Eckert et al, 2011), MyoD and NeuroD1 (Fong et al, 2012). Other non-bHLH EMT transcription factors, such as the Zn-finger homeodomain-containing factors Zeb1 and Zeb2, also function by binding to E-boxes and closely related Z-boxes (Burk et al, 2008).…”
Section: Wnt3a Regulates Emt and Psm Cell Motility Through Msgn1mentioning
confidence: 95%
“…Remarkably, studies of histone acetylation in the context of terminal differentiation have observed a near-complete loss of H3K9ac in contrast to a high level of H3K18ac on genes activated in myotubes as compared to proliferating myoblasts [4,16]. Furthermore, the association of MyoD to distinct E-box motifs generally corresponds to enhancer assembly, marked by H3K27ac, and muscle-specific gene expression during myotube formation [16,17]. As a result, MyoD binding is an index of myogenic enhancers [1], leading to the recruitment of histone acetyltransferases (HATs), which deposit the acetyl moiety required for enhancer activation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of myogenin is a key step in myogenic differentiation, and changes in DNA methylation patterns at this locus have been identified as differentiation proceeds and this gene is induced (Fuso et al 2010;Palacios et al 2010). DNA binding of MyoD and induction of muscle-determining genes is also regulated by epigenetic changes to binding sites in the promoters of its target genes (Fong et al 2012). Dynamic changes in DNA modification regulate myogenic commitment and differentiation (Tsumagari et al 2013), and global changes in DNA methylation patterns have been mapped in fast-and slow-growing strains of chicken, evidence for a direct epigenetic effect on muscle growth (Hu et al 2013b).…”
Section: Genetic Regulation Of Muscle Growthmentioning
confidence: 99%